Spectral and angular distributions of synchrotron radiation in quantum theory - Burimova, Anastasia (2014)
In the framework of quantum theory the characteristics of synchrotron radiation (SR) are considered. In order to simplify theoretical description the process of radiation is restricted to single-photon emission. For arbitrary quantum transitions the spectral-angular distributions of SR power are given in exact analytical form. Scalar particles (bosons) and particles with spin $\\hbar/2$ (electrons) are treated separately. Special attention is given to the particular transitions, namely, to the transitions to first excited and ground states. It is shown that the components of linear polarization of radiation from electron switch places due to the orientation of spin when the electron jumps to the ground state. This fact can be considered an analytical proof for the presence of $\\pi$-component of quantum radiation in the plane of motion. The radiation emitted from weakly excited particles is thoroughly analysed. To describe the evolution of the profiles of angular distributions various functions are introduced both for two- and three-level systems. For quantum transitions from the first excited state to the ground state the comparative analysis of radiation from bosons and electrons is performed, which helps to estimate the influence of spin and its direction on the characteristics of radiation. The radiation from unpolarized electron is considered separately. Tracking the behavior of effective angles allows to discover the inconsistency of well-known classical conclusion about the concentration of total (summed over spectrum) ultrarelativistic radiation in the plane of motion. It is shown that the effective angles of quantum radiation tend to finite values and do not vanish in ultrarelativistic region. A brief review of classical theory includes an introduction of the new concept, $n$-part of spectrum. In order to find an adequate classical analogue for the radiation from weakly excited particles, the idea to reduce classical spectrum was developed. It turns out that the characteristics of radiation calculated for reduced classical spectrum stay in good quantitative and qualitative agreement with their quantum analogues, at least for single-harmonic and two-harmonic quantum spectra, and classical theory of a reduced spectrum can be claimed representational in this sense. The evolution of maximum in radiation spectrum is considered in separate chapter. A well-known approximation obtained for critical frequency in the framework of classical theory is invalid when quantum corrections enter the picture. But there appears a possibility to find the conditions for the maximum to shift to the highest harmonic of finite quantum spectrum. It is shown that the shifts occur successively starting with primary harmonic in non-relativistic case, and this result remains valid independently of spin. For a scalar particle there exists a fixed set of numbers, which are the critical values of external field, such that the shift of radiation maximum in the spectrum of boson can only happen when the intensity of external field is greater than certain critical value related to corresponding harmonic. If this condition is not satisfied, the position of maximum remains unchanged. It turns out that the presence of spin perturbs this picture, so that the critical values of field intensity depend on the number of initial level.